Adapting to Indonesian Culture: Success Stories and Implications for Sustainable Expat Relocation - Davlyatbekovna, Nafisa Nazarova (Research Horizon, 2024)
The article examines the cultural adaptation of two expatriate families from Tajikistan and Kyrgyzstan who moved to Semarang, Indonesia. In the context of green value creation and sustainable economics, the aim is to identify key factors for successful adaptation and their impact on sustainable relocation. The study is conducted through surveys and interviews exploring the stages of cultural adaptation according to the U-curve theory: honeymoon, culture shock, adaptation and final integration. The results show successful overcoming of culture shock and comfortable integration of families into Indonesian culture, highlighting the importance of understanding cultural differences and similarities. The article highlights the economic and managerial aspects of cultural adaptation, which contributes to the development of effective HR strategies and sustainable business development. These aspects are important for economics, management and business faculties, as the successful integration of expatriates directly impacts the economic stability of the region and the achievement of Golden Indonesia 2045 goals.